DNA Sequence Alignment during Homologous Recombination - Greene, Eric C. (J Biol Chem, 2016)
Homologous recombination allows for the regulated exchange of genetic information between two different DNA molecules of identical or nearly identical sequence composition, and is a major pathway for the repair of double-stranded DNA breaks. A key facet of homologous recombination is the ability of recombination proteins to perfectly align the damaged DNA with homologous sequence located elsewhere in the genome. This reaction is referred to as the homology search and is akin to the target searches conducted by many different DNA-binding proteins. Here I briefly highlight early investigations into the homology search mechanism, and then describe more recent research. Based on these studies, I summarize a model that includes a combination of intersegmental transfer, short-distance one-dimensional sliding, and length-specific microhomology recognition to efficiently align DNA sequences during the homology search. I also suggest some future directions to help further our understanding of the homology search. Where appropriate, I direct the reader to other recent reviews describing various issues related to homologous recombination.